A "tax" on gender affirmation and safety: costs and benefits of intranational migration for transgender young adults in the San Francisco Bay area. Issue 12 (22nd November 2021) - Gamarel, Kristi E.; King, Wesley M.; Mouzoon, Raha; Xie, Hui; Stanislaus, Victorine; Iwamoto, Mariko; Baxter, Keanu; Suico, Sabrina; Nemoto, Tooru; Operario, Don
Abstract: Many transgender (trans) young adults migrate to urban enclaves with known infrastructures to fulfil gender affirmation needs such as obtaining trans-inclusive healthcare and support. This study sought to explore experiences of intranational migration (i.e. migration within a single country) for gender affirmation among trans young adults who relocated to San Francisco. A convenience sample of 61 trans young adults aged 18 to 29 (32% nonbinary, 28% trans women, and 40% trans men; 84% identified as a person of colour) participated in a one-time qualitative interview as part of a larger study. Thematic analysis was used to develop and refine the codes and themes. Three overarching themes became apparent regarding intranational migration and gender affirmation needs: (1) access to basic gender affirmation needs; (2) safety; and (3) the price of gender affirmation. Migration for gender affirmation and safety placed informants at risk for structural vulnerabilities including homelessness, unemployment and racism. Despite these structural vulnerabilities, participants were willing to "pay" the price in order to gain gender affirmation and safety. Findings underscore the importance of moving beyond individual-level risk factors to understand how unmet gender affirmation needs may place trans young adults in structurally vulnerable positions that can affect health and wellness.